The level of physical activity of preschoolers while they are in kindergarten during the summer - Sosunovskiy V.S. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to calculate the amount of physical activity engaged in by preschoolers during their time at a preschool facility during the summer and to compare it with the levels of activity observed in the fall, winter, and spring. Methods and structure of the study. To gather data on the physical activity of preschoolers, the researchers employed the method of pedometry. The number of locomotives was calculated using the Yamasa Corp., Yamax DW-200 Sh 25 pedometer, which was manufactured in Tokyo, Japan. The study examined the pedometer data of 234 children, including 132 children aged 5-6 (70 girls, 62 boys) and 102 children aged 3-4 (46 girls, 56 boys). Results and conclusions. Upon examining the data obtained through pedometry, it was observed that the level of physical activity among preschoolers during the summer was higher compared to the autumn, winter, and spring seasons. These findings provide valuable insights for the development of a more effective physical education and wellness program, taking into account the natural variations in children’s physical activity throughout the year. Introduction. Over the past decades, we have seen a change in children’s motor activity patterns, as they have become less likely to play outdoors due to a number of reasons: changing parental attitudes toward child safety, the influence of modern gadgets, etc. Therefore, modern parents, in order to avoid a deficit of motor activity in their children, offer them to attend various sports sections from preschool age [1, 3, 4, 5]. In this regard, the physical activity of modern children has changed its vector from independent, voluntary activities in the fresh air to structured, directive activities indoors. It is worth noting that this phenomenon is reflected not only in a decrease in the physical and functional indicators of children, but also often contradicts the basic provisions of preschool childhood, which is considered a unique period in the formation of a person’s personality. Also, in organized joint motor activity, there is no element of the formation of the child’s subjective position, because all motor activity is planned in advance and provided to the child by the teacher.